Limbah Cangkang Telur Sebagai Inovasi Material Pengganti Agregat Halus Beton - Bunyamin; Heru Pramanda; Nesri Hendrifa; Afdhal (Kadiri University, 2023)
Eggshells become a huge waste and cause various environmental problems. One of the efforts that can be made to reduce this waste is to use it as a material in concrete. Cement and fine aggregate raw materials that are continuously used will eventually run out and are difficult to renew. This study aims to determine the slump value and compressive strength using eggshell waste as a substitute for cement and fine aggregate in concrete. Eggshells as a substitute for cement were in the oven at 105°C for 24 hours and then fired and the material that passed the No. sieve was taken. 200 (75 µm) and sieve number 4 for fine aggregate. The percentage of mixed eggshell content used was 0%, 5%, 10%, and 15%. The results showed that the slump and compressive strength decreased with increasing eggshell content in the concrete. This is caused by the size of the eggshell. The use of egg shells with a size of 4.75 mm as a substitute for fine aggregate is not recommended for concrete. The irregular shape of the eggshell is considered less capable of filling cavities and even causing cavities in concrete. The right size for using egg shells is in the range of 0.5 – 1 mm. Referring to these results, this study highlights the importance of choosing eggshell size as a substitute for fine aggregate. So that with proper utilization, egg shells can be utilized as a material substitute and improve the quality of concrete.